Effects of long-term self-massage at the musculotendinous junction on hamstring extensibility, stiffness, stretch tolerance, and structural indices: A randomized controlled trial. (September 2016) - Akazawa, Naoki; Okawa, Naomi; Kishi, Masaki; Nakatani, Kiyoshi; Nishikawa, Katsuya; Tokumura, Daichi; Matsui, Yuji; Moriyama, Hideki
Abstract: Objectives: The purpose of this study was to examine the effect of long-term self-massage at the musculotendinous junction on hamstring extensibility, stiffness, stretch tolerance, and structural indices. Design: Single-blind, randomized, controlled trial. Setting: Laboratory. Participants: Thirty-seven healthy men. Intervention: The right or left leg of each participant was randomly assigned to the massage group, and the other leg was assigned to the control group. The participants conducted self-massage at the musculotendinous junction for 3 min daily, five times per week, for 12 weeks. Main outcome measures: Hamstring extensibility, stiffness, stretch tolerance, and structural indices were measured by a blinded examiner prior to the massage intervention and after 6 and 12 weeks of intervention. Results: The maximum hip flexion angle (HFA) and the maximum passive pressure after 6 and 12 weeks of intervention in the massage group were significantly higher than prior to intervention. The visual analog scale (for pain perception) at maximum HFA, the stiffness of the hamstring, and the structural indices did not differ in either group over the 12 week period. Conclusions: Our results suggest that long-term self-massage at the musculotendinous junction increases hamstring extensibility by improving stretch tolerance. However, this intervention does not change hamstring stiffness. Clinical trial registration number: University Hospital Medical Information Network registration numberUMIN000011233 . Highlights: Long-term self-massage may increase hamstring extensibility and stretch tolerance. Long-term self-massage does not change hamstring stiffness and muscle structure. Twelve weeks of massage have a greater effect on stretch tolerance than 6 weeks.